O ético e o estético em Adorno - Farinon, Mauricio João (2012)
Ethics, aesthetic and education are the basic concepts in this present investigation, which has as its guiding paradigm, critical theory of Theodor Adorno. Form the basis the allow us to conceive the post-metaphysical subject in Adorno, under what conditions is possible defend the enlargement of the experience like a way of the constitution of the subjectivity, which is the basis of the moral consciousness, and that ethic signification comes to the education, in view of the subject that, morally, need to be constituted based on the experience? Starting from this problem, the general goal is to discuss the post-metaphysical subjectivity notion in Adorno, to establish, based in such subject, an ethical and educational meaning, able to guide the human formation and the moral consciousness development. As theoretical indicative, the thesis proposes that, in the moment that the education becomes an enrichment promoter of the formation experiences, is possible the enlargement of the way that happens the constitution and the development of the ethic subject. This guides us to the constitution of the environment in which the mankind is inside, this environment is called language. Therefore, the defense is about the linguistic shape as the ethical challenge of human development.It is articulated the aesthetic as a foundation under which is possible to defend the enlargement of the concept of the experience and the constitution of the subjectivity. The theoretical approach starts with a discussion on how the constitution of subjectivity and moral consciousness in Kant happens, whose foundation lies in the concepts of order and freedom, to, after, understand the change proposed by Adorno, in which aesthetics is intimately related to ethics, as is evident from the terms of concrete constellation, communication and real content. The method is analytical and conceptual, creating a confrontation between these two philosophical strands, while proposing significance to educational practice in the school environment. The propose o recognize the other as a concrete, who is inserted in a linguistic environment, and the necessity for the classroom to be an ideal place in which this environment should be shaped, is an ethical alternative to the formation, from which we can glimpse the school as a place of development and qualification of the human.